Efficacy of an 8-Week Concurrent Strength and Endurance Training program on Hand Cycling Performance. Issue 7 (July 2018) - Nevin, Jonpaul; Smith, Paul; Waldron, Mark; Patterson, Stephen; Price, Mike; Hunt, Alex; Blagrove, Richard
Abstract : Abstract: Nevin, JP, Smith, P, Waldron, M, Patterson, S, Price, M, Hunt, A, and Blagrove, R. Efficacy of an 8-week concurrent strength and endurance training program on hand cycling performance. J Strength Cond Res 32(7): 1861–1868, 2018—The aim of this study was to investigate the effects of an 8-week concurrent strength and endurance training program in comparison with endurance training only on several key determinants of hand cycling performance. Five H4 and 5 H3 classified hand cyclists with at least 1 year's hand cycling training history consented to participate in the study. Subjects underwent a battery of tests to establish body mass, body composition, V[Combining Dot Above]O2 peak, maximum aerobic power, gross mechanical efficiency (GME), maximal upper-body strength, and 30-km time-trial performance. Subjects were matched into pairs based on 30-km time-trial performance and randomly allocated to either a concurrent strength and endurance or endurance training only, intervention group. After an 8-week training program based on a conjugated block periodization model, subjects completed a second battery of tests. A mixed model, 2-way analysis of variance revealed no significant changes between groups. However, the calculation of effect sizes (ESs) revealed that both groups demonstrated a positive improvement in most physiological and performance measures with subjects in the concurrent group demonstrating a greater magnitude of improvement in body composition (ES −0.80 vs. −0.22), maximal aerobic power (ES 0.97 vs. 0.28), GME (ES 0.87 vs. 0.63), bench press 1 repetition maximum (1RM) (ES 0.53 vs. 0.33), seated row 1RM (ES 1.42 vs. 0.43), and 30-km time-trial performance (ES −0.66 vs. −0.30). In comparison with endurance training only, an 8-week concurrent training intervention based on a conjugated block periodization model seems to be a more effective training regime for improving the performance capabilities of hand cyclists.